2018
DOI: 10.3390/su10082855
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Types of Plug-In Charging Facilities’ Location-Routing Problem with Time Windows for Mobile Charging Vehicles

Abstract: Abstract:Increasing attention is being paid to the technology of battery electric vehicles (BEVs) because of their environmental friendliness. However, their short range, extended recharging times, and insufficient charging facilities hinder the improvement in the market share of BEVs. As a remedy, this paper presents a novel approach to providing a service for the battery charge replenishment of BEVs. Instead of using traditional alternative methods by only providing a charging service in a fixed location, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…A linear form of condition (11) can be obtained similarly to those obtained for (9) and (10). Assuming service times in each service center are exponentially assigned with a mean serving rate µ j > 0, to have a balance in the system, we have the condition µ j ≥ m j λ j where m j represents the number of mobile stations of center j, and λ j is the intensity of the Poisson process of charge requests arriving to center j. Marianov and Serra [45] showed that…”
Section: Linear Optimization Problemmentioning
confidence: 97%
See 4 more Smart Citations
“…A linear form of condition (11) can be obtained similarly to those obtained for (9) and (10). Assuming service times in each service center are exponentially assigned with a mean serving rate µ j > 0, to have a balance in the system, we have the condition µ j ≥ m j λ j where m j represents the number of mobile stations of center j, and λ j is the intensity of the Poisson process of charge requests arriving to center j. Marianov and Serra [45] showed that…”
Section: Linear Optimization Problemmentioning
confidence: 97%
“…The routing problem that arises with the current operational mode of a mobile charging station was also analyzed in the literature. Two decisions (location and routing) with time-windows were investigated in [11], with the results showing a need for a more efficient service in the sense of improving the charging rate or increasing battery capacity. Similar results were obtained by Cui et al in 2018 [12] by modeling the routing problem of a mobile charging station as a mixed-integer linear problem with time windows.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations